2012
DOI: 10.1007/s00330-012-2434-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of stress myocardial perfusion imaging for coronary artery disease: a systematic review and meta-analysis

Abstract: ObjectivesTo determine and compare the diagnostic performance of stress myocardial perfusion imaging (MPI) for the diagnosis of obstructive coronary artery disease (CAD), using conventional coronary angiography (CCA) as the reference standard.MethodsWe searched Medline and Embase for literature that evaluated stress MPI for the diagnosis of obstructive CAD using magnetic resonance imaging (MRI), contrast-enhanced echocardiography (ECHO), single-photon emission computed tomography (SPECT) and positron emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
3
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 62 publications
0
87
3
12
Order By: Relevance
“…[16][17][18][19]30,31 Adenosine stress perfusion CMR is highly sensitive, specific, and reproducible for identification of obstructive CAD and has been reported to be superior to other stress imaging methods for this purpose. [32][33][34][35][36][37][38] In the setting of stable, nonobstructive CAD, patients with proven microvascular disease based on invasive coronary reactivity testing had lower MPRI as compared with healthy controls. 39 In our study, when stress perfusion was abnormal in patients with LGE or T2+, abnormal perfusion was typically identified in the affected myocardial segments.…”
Section: Cmr Evidence Of Infarction (Lge)mentioning
confidence: 99%
“…[16][17][18][19]30,31 Adenosine stress perfusion CMR is highly sensitive, specific, and reproducible for identification of obstructive CAD and has been reported to be superior to other stress imaging methods for this purpose. [32][33][34][35][36][37][38] In the setting of stable, nonobstructive CAD, patients with proven microvascular disease based on invasive coronary reactivity testing had lower MPRI as compared with healthy controls. 39 In our study, when stress perfusion was abnormal in patients with LGE or T2+, abnormal perfusion was typically identified in the affected myocardial segments.…”
Section: Cmr Evidence Of Infarction (Lge)mentioning
confidence: 99%
“…Coronary CT angiography serves as an excellent anatomic gatekeeper as it has a very high negative predictive value, while stress perfusion cardiac MRI is a regarded as a physiologic gatekeeper. Stress perfusion cardiac MRI has been proved to be a robust and accurate diagnostic test for CAD when invasive coronary angiography is used as the reference standard [25][26][27][28]. Several systematic reviews and meta-analyses have shown that the sensitivity and specificity of stress perfusion MRI ranged from 89% to 91% and 76% to 81%, using invasive coronary angiography as the reference standard [26][27][28].…”
Section: Journal Ofmentioning
confidence: 99%
“…Stress perfusion cardiac MRI has been proved to be a robust and accurate diagnostic test for CAD when invasive coronary angiography is used as the reference standard [25][26][27][28]. Several systematic reviews and meta-analyses have shown that the sensitivity and specificity of stress perfusion MRI ranged from 89% to 91% and 76% to 81%, using invasive coronary angiography as the reference standard [26][27][28]. Desai and Jha recently conducted a meta-analysis of 12 studies regarding the cardiac stress perfusion MRI in the diagnosis of flow-limiting obstructive CAD using fractional flow reserve measured at invasive coronary angiography as the reference standard [29].…”
Section: Journal Ofmentioning
confidence: 99%
“…
Dear Editor, I was disappointed to realise that in the recent meta-analysis published online ahead of print in your journal, entitled "Diagnostic performance of stress myocardial perfusion imaging for coronary artery disease: a systematic review and meta-analysis" by de Jong et al [1], the single numerically most relevant prospective diagnostic study in the contrast stress-echo field, which I co-authored [2], comprising 400 patients and published in 2010 (in time for being included), was not cited and its data not included in the meta-analysis; this is a relevant mistake, first made by the authors in the data selection process and then by the reviewers in accepting such severely incomplete data: inevitably this makes the meta-analysis results and conclusions deeply flawed.All inclusion/exclusion criteria, clearly stated in the methods section, are fulfilled by our above-mentioned study, and it could not be otherwise, since that is one of the few prospective and multicentre studies in the contrast stress-echocardiography field, conducted on patients with a previous clinical indication to angiography, so that verification bias is not an issue. Data regarding stress myocardial perfusion accuracy were easily available in numerical table format and readily at hand in our study.
…”
mentioning
confidence: 99%
“…Dear Editor, I was disappointed to realise that in the recent meta-analysis published online ahead of print in your journal, entitled "Diagnostic performance of stress myocardial perfusion imaging for coronary artery disease: a systematic review and meta-analysis" by de Jong et al [1], the single numerically most relevant prospective diagnostic study in the contrast stress-echo field, which I co-authored [2], comprising 400 patients and published in 2010 (in time for being included), was not cited and its data not included in the meta-analysis; this is a relevant mistake, first made by the authors in the data selection process and then by the reviewers in accepting such severely incomplete data: inevitably this makes the meta-analysis results and conclusions deeply flawed.…”
mentioning
confidence: 99%